1994
DOI: 10.1029/93ja02903
|View full text |Cite
|
Sign up to set email alerts
|

Auroral latitude Pc 5 field line resonances: Quantized frequencies, spatial characteristics, and diurnal variation

Abstract: On the basis of observations with the Goose Bay Radar, several stations of the the Canadian Auroral Network for the Origin of Plasmas in the Earth's Neighborhood (OPEN) Unified Study (CANOPUS) magnetometer array, and a CANOPUS meridian scanning photometer, recent work has indicated the existence of Pc 5 ULF waves with discrete and remarkably stable frequencies (1.3, 1.9, 2.7 and 3.3 mHz with <10% variation) in the local midnight and early morning (predawn) sectors. These ULF waves were interpreted as the conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

24
92
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 28 publications
24
92
0
Order By: Relevance
“…∼0.1 mHz). On the other hand, Ziesolleck and McDiarmid (1995) and, more recently, Mathie et al (1999) suggested that there is no unique set of waveguide mode frequencies; the CMS are dominant against a background spread of frequencies.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…∼0.1 mHz). On the other hand, Ziesolleck and McDiarmid (1995) and, more recently, Mathie et al (1999) suggested that there is no unique set of waveguide mode frequencies; the CMS are dominant against a background spread of frequencies.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Pioneering investigations by several authors Samson et al, 1991Samson et al, , 1992Walker et al, 1992;Ziesolleck and McDiarmid, 1994) reported evidence at auroral latitudes of long period ULF waves in F-region drift velocities and in the local geomagnetic field components at discrete frequencies (of the order of 1.3, 1.9, 2.6 and 3.4 mHz). According to the theoretical suggestions provided by Radoski (1974) and extended by Southwood (1985, 1986), these modes were interpreted in terms of field line resonances driven by compressional modes of the magnetosphere which would act as a resonant cavity (with eigenfrequencies depending on its dimensions and physical characteristics) when excited by external mechanisms such as pressure pulses of the solar wind (SW).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Samson et al (1992) and Ziesolleck and McDiarmid (1994) showed that these peaks of power can also be identified in the simultaneous fluctuations of the local ground magnetic field. These events typically are of long duration, have stable frequencies (within 10%) and most frequently occur near local midnight and in the very early morning, although Ziesolleck and McDiarmid (1994) recently proposed similar observations in the dayside hemisphere. Following the original suggestion by Kivelson and Southwood (1985), these oscillations are currently interpreted in terms of field line resonances excited by compressional modes of the magnetospheric cavity Walker et al, 1992).…”
Section: Introductionmentioning
confidence: 95%
“…Thus the significance of these observations has been open to debate. Ziesolleck and McDiarmid (1994) employed ground-magnetometer data in search of these monochromatic field-line resonances, but their results proved inconclusive. In view of this a study of the data from the SABRE (Nielsen et al, 1983) radar at Wick has been undertaken to establish whether observations taken from a lower latitude, at a different longitude and with a different radar system would exhibit the same structured spectra.…”
Section: Introductionmentioning
confidence: 99%